Removal of total suspended solid (tss) and chemical oxygen demand (cod) in oleochemical wastewater using electrocoagulation treatment - Faten Ahada, Mohd Azli (2023)
Wastewater from oleochemical industry contains high concentration glycerin, chemical oxygen demand (COD) and total suspended solids (TSS) that can cause environmental pollution if discharged without proper treatment method. Currently, oleochemical industry uses reverse osmosis membrane and submerges bed biofilm reactor to treat their wastewater. In this work, other method namely electrocoagulation treatment that capable to achieve a high removal of color, COD, biological oxygen demand (BOD) is employed. Electrocoagulation have been used in many industrial sectors to treat wastewater before discharged and success in treating different types of wastewaters such as urban wastewaters, textile industries, laundry wastewater, restaurant wastewater, electroplating wastewater, chemical, mechanical, polishing wastewater, olive mill wastewater, dairy and tannery wastewater, pulp and paper mill industry wastewater, baker’s yeast wastewater and slaughterhouse wastewater. Response surface methodology (RSM) is used to optimize the operating parameters for the process. RSM is conducted by using software with two-factor, three-level central composite design (CCD). Besides, it is also used to identify the interaction between each parameters and to get the optimum values of the parameter that affect the process. The optimization study has been conducted using design of expert version 7.0. The objective of the study was to determine the characteristics of oleochemical wastewater quality from oleochemical industry and to evaluate the effect of parameter whereas pH (6-9), type of electrode (aluminium & stainless steel), applied current (4.0-8.0A), retention time (10-40min) and arrangement of electrode (bipolar & monopolar) in electrocoagulation performance in treating wastewater to reduce chemical oxygen demand (COD) and total suspended solid (TSS) in wastewater from an oleochemical industry using this process. The experimental results showed that the pollutant removal efficiencies of COD and TSS can be achieved at 62.64% and 66.12%, respectively, of the initial concentration of parameters using aluminium electrode at the optimum conditions of pH 7.5, applied current 6A and reaction time of 30 min. Treating oleochemical wastewater using electrocoagulation reactor at the optimum parameter reduced COD from 87,000ppm to 38,700ppm about 55.52% after 35 min. All the findings of the study revealed that the treatment of oleochemical wastewater by electrocoagulation process at the optimum conditions can be applied as an alternative treatment.